Gomez Pereira's Antoniana margarita : a work on natural philosophy, medicine and theology - García Valverde, José Manuel,; García Valverde, José Manuel,; Maxwell-Stuart, P. G.,; Maxwell-Stuart, P. G.,; Pereira, Gometius, 1500-; Pereira, Gometius, 1500- (Novum Testamentum, Supplements;, 2019)
Nearly a century before Descartes, Gómez Pereira published the Antoniana Margarita with the purpose of demonstrating the thesis of animal automatism, among many other things. The author included in his book several proofs of animal insensitivity and an original model aimed at explaining animal behaviour in the grounds of a purely mechanical system. In this sense, Pereira's work represents a critical appraisal of the traditional scholastic theory of the animal mind, as well as one of the first efforts to develop this question in the field of empirical observation and physio¬logical knowledge. It is precisely for this reason that Gómez Pereira must be recognized as one of the most valuable thinkers of the Spanish Renaissance. The editors, García Valverde and Maxwell-Stuart, offer the first critical edition of the Latin text, a careful translation and an extensive study that contextualizes its content in the philosophy of the sixteenth century.